2021
DOI: 10.3390/cancers13040627
|View full text |Cite
|
Sign up to set email alerts
|

Remission-Stage Ovarian Cancer Cell Vaccine with Cowpea Mosaic Virus Adjuvant Prevents Tumor Growth

Abstract: Ovarian cancer is the deadliest gynecological malignancy. Though most patients enter remission following initial interventions, relapse is common and often fatal. Accordingly, there is a substantial need for ovarian cancer therapies that prevent relapse. Following remission generated by surgical debulking and chemotherapy, but prior to relapse, resected and inactivated tumor tissue could be used as a personalized vaccine antigen source. The patient’s own tumor contains relevant antigens and, when combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…CPMV has unique potency and it outperforms classical adjuvants as well as other plant viruses . CPMV is more potent compared to small-molecule TLR or STING agonists. , This can be explained by the nanoparticle character enabling prolonged tumor retention and multivalent and multipronged engagement of TLR receptors. , Hence, CPMV offers advantages compared to synthetic small-molecule therapeutics because it mimics a viral pathogen or danger signal more closely. Additional advantages are conferred over mammalian oncolytic therapies: production through plant molecular farming is highly scalable and high yielding; 1 mg of CPMV can be obtained per 1 g of infected leaf tissue.…”
Section: Resultsmentioning
confidence: 99%
“…CPMV has unique potency and it outperforms classical adjuvants as well as other plant viruses . CPMV is more potent compared to small-molecule TLR or STING agonists. , This can be explained by the nanoparticle character enabling prolonged tumor retention and multivalent and multipronged engagement of TLR receptors. , Hence, CPMV offers advantages compared to synthetic small-molecule therapeutics because it mimics a viral pathogen or danger signal more closely. Additional advantages are conferred over mammalian oncolytic therapies: production through plant molecular farming is highly scalable and high yielding; 1 mg of CPMV can be obtained per 1 g of infected leaf tissue.…”
Section: Resultsmentioning
confidence: 99%
“…22,24 We have demonstrated efficacy of CPMV as solo-treatment and in combination with radiation, 25 chemotherapy, 26 and checkpoint inhibitors. 27 Importantly, we found that CPMV has unique potency when used as ISV, that is, used as immunostimulatory agent administered directly into a tumor, compared to other nonrelated plant viruses, bacteriophage VLPs or mammalian VLPs, 28 or small molecule adjuvants 17,29 in terms of immune activation mechanisms and antitumor efficacy. Specifically, we compared efficacy and mechanism of immune activation of CPMV versus tobacco mosaic virus, 16 potato virus X, 30 cowpea chlorotic mottle virus, physalis mosaic virus-like particles, sesbania mosaic virus, Qβ phage VLPs, and Hepatitis B core particles 28 and data show while all virus-based nanoparticles are immunogenic, only CPMV-ISV primes potent antitumor immunity.…”
Section: ■ Introductionmentioning
confidence: 94%
“…Additionally, VLPs can also be adopted in combination with ICIs to increase the therapeutic effect of immunotherapy. [90,91] For example, Gautam et al covalently linked the PD-1 antibody peptide (SNTSESF) to CPMV for OC immunotherapy. [92] SNTSESF, also known as AUR-7, is a potent ICI mimicking the endogenous PD-1 receptor to inhibit PD-1 function.…”
Section: Nanocomposite-based Vaccinesmentioning
confidence: 99%
“…Additionally, VLPs can also be adopted in combination with ICIs to increase the therapeutic effect of immunotherapy. [ 90 , 91 ] For example, Gautam et al. covalently linked the PD‐1 antibody peptide (SNTSESF) to CPMV for OC immunotherapy.…”
Section: Nanovaccines “Heating” Ocmentioning
confidence: 99%